Rancang Bangun Smart Nurse Call (Pemanggil Perawat) Berbasis Android - Pradita Ghanda Septian (Politeknik Negeri Malang, 2019)
The limited number of nurses is a problem that often occurs in the world of health which has an impact on the high workload of nurses resulting in less optimal patient care and decreased patient satisfaction. According to Institute for Healthcare Improvement, nurses spend only 20-30% of their time in direct patient care, the rest on documentation and administration processes. So, hospitals generally provide nurse calls so families don't have to leave patients to find nurses.The purpose of this study was to make it easier for patients to use Smart Nurse Call, especially for patients with acute diagnosis conditions and it's easier for nurses to monitor patient's condition. It's also examines the distance of data transmission in one building to determine the performance of wireless (access points).Based on data from test results, the quality of data transmission using wireless media is known that access point has data transmission limit. In testing distance at AH building stated that data transmission based on the range on the 1st floor is able to reach the entire corridor, for 2nd floor it can reach a distance of 13 meters while on 3rd floor it cannot be reached. The data from suitability test of smart nurse call tool showed that the suitability level of the device was quite high and almost same as manual test at 97.65%. The data from stress test results from push button get average voltage value low position at 0 V and average high voltage at 4.675 V.